The efficacy and safety of anti‐tumor necrosis factor agents in the treatment of intestinal Behcet's disease, a systematic review and meta‐analysis - Zhang, Mengyuan; Liu, Jinjing; Liu, Tingting; Han, Wei; Bai, Xiaoyin; Ruan, Gechong; Lv, Hong; Shu, Huijun; Li, Yue; Li, Ji; Tan, Bei; Zheng, Weiyang; et al. (Journal of gastroenterology and hepatology, 2022)
Background and Aim Behcet's disease is a systemic vasculitis that can involve gastrointestinal tract. This is a systematic review and meta‐analysis evaluating the efficacy and safety of anti‐tumor necrosis factor (TNF) agents in treating patients with intestinal Behcet's disease. Methods We conducted searches on PubMed, Embase, and Cochrane. Data from eligible studies were used to calculate the pooled estimate of proportions of clinical remission, mucosal healing at Months 3, 6, 12, and 24 as well as the pooled incidence of adverse drug reactions. And subgroup analysis based on the specific type of anti‐TNF agents was performed. Results Of the 828 studies initially identified, 13 were included finally, all of which were single‐arm cohort studies. The pooled proportions of clinical remission at Months 3, 6, 12, and 24 were 0.61 (95%CI 0.48–0.78), 0.51 (95%CI 0.40–0.66), 0.57 (95%CI 0.48–0.67), and 0.38 (95%CI 0.16–0.88), respectively. The pooled proportions of mucosal healing at Months 3, 6, 12, and 24 were 0.66 (95%CI 0.50–0.86), 0.82 (95%CI 0.48–0.98), 0.65 (95%CI 0.51–0.81), and 0.69 (95%CI 0.39–1.00), respectively. The pooled estimate of proportion of overall adverse drug reactions for infliximab was 0.22 (95%CI 0.07–0.69). Conclusions Anti‐TNF agents, including infliximab and adalimumab, were an efficient therapy for intestinal Behcet's disease. The safety of anti‐TNF agents used in the treatment of intestinal Behcet's disease was acceptable.